ANALISIS KONTRIBUSI PERPUSTAKAAN PERGURUAN TINGGI DALAM MENINGKATKAN PRESTASI AKADEMIK MAHASISWA - Andi Saputra (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
Introduction. This study aims to measure the extent of the contribution of libraries in sustaining the tri dharma of higher education, by analyzing the activities of students in the library while undergoing lectures with academic achievement (GPA and study period).Data collection method. Research location at the Andalas University Library Unit. The data collection method is done by purposive sampling, based on certain criteria, such as year of entry, level of education, as well as the distance between faculty and library. The study sample was taken from data on the number of visits and the number of student loan collections during the course, which were used as the dependent variable. Whereas academic achievement (independent variable) is measured by GPA and graduate study period.Data analysis. In conducting the analysis, respondents are grouped into 5 categories using a Likert scale, based on the number of visits and the number of books borrowed. After that, the effect on the GPA and the study period was tested using the ANOVA method with the SPSS version 23 application test tool.Results and Discussion. The test results of influence the number of visitors to the GPA produce a significant value of 0,000, and the effect on the study period produces a value of 0.590. While the influence of the number of loans to the GPA produces a significant value of 0,000, and the effect on the study period is 0.230, with a significant limitation of 0.05Conclusions and recommendations. Based on the results of this study it was concluded that the level of visits and utilization of library collections on the Andalas University campus were still very low. Though these activities significantly influence the increase in student GPA but not for the study period.